2D/3D biometric and biomedical image matching using line constraints - Li, Fang (2013)
The work reported in this thesis is a research on 2D and 3D biometric and biomedical image registration, which is of current interest. Three body parts (palmprint, hand veins, and brain surfaces) identification/ registration have been investigated in this research. The three parts are selected from three categories (outer surface, beneath the skin, and internal organ). The goal of the research is to develop 2D/3D algorithms for robust and effective matching in palmprint/vein identification systems or surface registration.